2022
DOI: 10.1039/d2cy00030j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-temperature CeO2 calcination on the activity of Pt/CeO2 catalysts for oxidation of unburned hydrocarbon fuels

Abstract: High temperature (800 °C) pre-calcination of CeO2 support decreases the surface defects and improves the mobility of surface lattice oxygen. As a result, the supported Pt clusters have higher oxygen coverage and superior HC oxidation activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…As a reducible support, cerium dioxide (CeO 2 ) has received considerable attention from academia and industry, [1][2][3][4][5] attributed to the excellent oxygen storage capacity and abundant surface oxygen vacancy sites of CeO 2 . Supported metal nanoparticles on CeO 2 exhibit excellent activities for various reactions such as preferential oxidation of CO, [6][7][8] lowtemperature water-gas shift reaction, 9,10 CO/CO 2 hydrogenation to methanol, 11,12 etc.…”
mentioning
confidence: 99%
“…As a reducible support, cerium dioxide (CeO 2 ) has received considerable attention from academia and industry, [1][2][3][4][5] attributed to the excellent oxygen storage capacity and abundant surface oxygen vacancy sites of CeO 2 . Supported metal nanoparticles on CeO 2 exhibit excellent activities for various reactions such as preferential oxidation of CO, [6][7][8] lowtemperature water-gas shift reaction, 9,10 CO/CO 2 hydrogenation to methanol, 11,12 etc.…”
mentioning
confidence: 99%
“…In the ST process, high-temperature calcination could also affect the defect structure and stability of ceria. 41 To demonstrate that the presence of the OH groups is the major factor promoting catalytic performance, another control sample was prepared to calcine A-CeO 2 under the same ST conditions, but without steam, denoted as A-CeO 2 -750, to investigate the calcination effects of A-CeO 2 . The final obtained composite Pd catalyst was recorded as Pd_A-750.…”
Section: Resultsmentioning
confidence: 99%
“…There were recent reports that activity for CO and hydrocarbon oxidation can be enhanced over a Pt/CeO 2 catalyst when the support material was calcined at a high temperature (800 °C) due to a weaker metal−support interaction. 13,14 To further investigate the catalysis in our work, we calcined the support material at temperatures lower (450 and 750 °C) and higher than 800 °C (900 and 1000 °C). We primarily compared two catalysts with supports calcined at 450 and 1000 °C (labeled as C450 and C1000, respectively) by in situ XPS and confirmed that the C1000-containing catalyst can be more reducible than the C450-containing catalyst.…”
Section: ■ Introductionmentioning
confidence: 99%
“…CO generation over Co-based catalysts with a low metal loading of less than 2 wt % has been extensively demonstrated. , Prior studies suggested that CO was generated not only by CO 2 dissociation over reduced CeO 2– x with oxygen vacancies but also by formate decomposition at the metal–support interface or even over the metal nanoparticle smaller than 5 nm due to a weak H adsorption and perturbed hydrogenation to CH 4 . , However, in this study, we investigated the effect of the support particle size on CO 2 hydrogenation over Co/CeO 2 catalysts containing 5 wt % of Co, which is conventionally considered to produce CH 4 selectively, , and demonstrated an enhanced CO selectivity over the catalyst with CeO 2 support calcined at 1000 °C with an average particle size of ∼192 nm. There were recent reports that activity for CO and hydrocarbon oxidation can be enhanced over a Pt/CeO 2 catalyst when the support material was calcined at a high temperature (800 °C) due to a weaker metal–support interaction. , To further investigate the catalysis in our work, we calcined the support material at temperatures lower (450 and 750 °C) and higher than 800 °C (900 and 1000 °C). We primarily compared two catalysts with supports calcined at 450 and 1000 °C (labeled as C450 and C1000, respectively) by in situ XPS and confirmed that the C1000-containing catalyst can be more reducible than the C450-containing catalyst.…”
Section: Introductionmentioning
confidence: 99%